2016
DOI: 10.1371/journal.pone.0168189
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Surveillance Performance of Alpha-Fetoprotein by Selection of Proper Target Population in Chronic Hepatitis B

Abstract: Although alpha-fetoprotein (AFP) is the most widely used biomarker in hepatocellular carcinoma (HCC) surveillance, disease activity may also increase AFP levels in chronic hepatitis B (CHB). Since nucleos(t)ide analog (NA) therapy may reduce not only HBV viral loads and transaminase levels but also the falsely elevated AFP levels in CHB, we tried to determine whether exposure to NA therapy influences AFP performance and whether selective application can optimize the performance of AFP testing in CHB during HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…This may also imply a potential use of AKR1B10 for evaluation of tumor burden, metastasis, and/or recurrence of HCC. Like literature reports, AFP increased in patients with HCC recruited in this study, but AKR1B10 showed much better diagnostic accuracy for HCC than AFP.…”
Section: Discussionsupporting
confidence: 75%
“…This may also imply a potential use of AKR1B10 for evaluation of tumor burden, metastasis, and/or recurrence of HCC. Like literature reports, AFP increased in patients with HCC recruited in this study, but AKR1B10 showed much better diagnostic accuracy for HCC than AFP.…”
Section: Discussionsupporting
confidence: 75%
“…This indeed is not what has been found in our patients who, in the vast majority of cases, presented with early, small, single HCC—as high as 92%, with 93% of our patients within “Milan criteria”—assuring the best treatment options (curative treatment options offered to 78% of our patients) and the best prognosis. This is an unprecedented finding for Caucasian cirrhotic patients as the only other similar, but smaller in size, studies came from Korea and Hong‐Kong . There are several possible explanations for this finding.…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies suggest the performance of AFP can be optimized by stratifying the population under surveillance by etiology, receipt of therapy for chronic viral hepatitis – which may influence hepatic inflammation and liver regeneration, and liver synthetic function as measured by serum albumin [1315]. Further, recent studies also suggest that performance of liver US, which has been considered the more sensitive and specific screening modality, may not be as high in real-life practice as previously thought [16].…”
Section: Introductionmentioning
confidence: 99%